PENGARUH KESADARAN WAJIB PAJAK, SANKSI PAJAK DAN PELAYANAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PADA KANTOR PELAYANAN PAJAK PRATAMA CILEUNGSI, KABUPATEN BOGOR - Muhlis Muhlis; Novi Trisna (Institut Teknologi dan Bisnis Dewantara, 2020)
This research is aimed to investigate the effect of taxpayer awareness, tax sanctions, and tax services on individual taxpayer compliance at the Pratama Cileungsi tax service office, Bogor regency. The population of this study is an individual taxpayer. This research used Accidental Sampling technique, amounting to 100 samples. The results showed that tax sanctions had a significant effect on the level of compliance. The results of the t test on the tax sanctions variable (X2) obtained t count of 5.505. The t test result for the tax sanction variable was 5.505> 1.985 with a significance level of 0.000 <0.5. The results of the value of Fcount> Ftable or 13.615> 2.36 collectively, the taxpayer awareness variable, tax sanctions and, tax services have a significant effect on individual taxpayer compliance. Linear regression test results obtained Y = 15.072 + 0.030 X1 + 0.607 X2 + 0.030 X3 + e. The result of the coefficient of determination test shows that the R Square value is 29.8 percent.